2011
DOI: 10.1016/j.molcel.2011.06.019
|View full text |Cite
|
Sign up to set email alerts
|

ATR Autophosphorylation as a Molecular Switch for Checkpoint Activation

Abstract: The ataxia telangiectasia-mutated and Rad3-related (ATR) kinase is a master checkpoint regulator safeguarding the genome. Upon DNA damage, the ATR-ATRIP complex is recruited to sites of DNA damage by RPA-coated single-stranded DNA and activated by an elusive process. Here, we show that ATR is transformed into a hyperphosphorylated state after DNA damage, and that a single autophosphorylation event at Thr 1989 is crucial for ATR activation. Phosphorylation of Thr 1989 relies on RPA, ATRIP, and ATR kinase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
231
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(245 citation statements)
references
References 61 publications
14
231
0
Order By: Relevance
“…v-Src suppressed Rad17 phosphorylation (Fig. 6C) (86) induced by thymidine (data not shown), indicating that replication stress is induced. Furthermore, we confirmed that v-Src suppresses Chk1 phosphorylation without affecting thymidine arrest.…”
Section: Discussionmentioning
confidence: 80%
“…v-Src suppressed Rad17 phosphorylation (Fig. 6C) (86) induced by thymidine (data not shown), indicating that replication stress is induced. Furthermore, we confirmed that v-Src suppresses Chk1 phosphorylation without affecting thymidine arrest.…”
Section: Discussionmentioning
confidence: 80%
“…8) and emphasize the role of posttranslational acetylation in the regulation of Sirt1 activity. Autocatalytic modifications of proteins are common and have been primarily described for kinases (30), acetyltransferases (31), and also for phosphatases (32) but not for deacetylases. An involvement of acetylation/deacetylation in the regulation of enzymatic activity of this class of proteins has mostly remained enigmatic, although acetylation of several protein deacetylases has been reported previously (33).…”
Section: Discussionmentioning
confidence: 99%
“…ATR has been shown to phosphorylate itself on Thr1989 in asynchronous populations of cells exposed to inducers of replication stress (43,44). To determine whether this residue becomes phosphorylated in non-replicating cells, I exposed both cycling and non-cycling cells to NA-AAF and then monitored Thr1989 phosphorylation by immunoblotting.…”
Section: Atr Autophosphorylation On Thr1989 In Noncycling Cellsmentioning
confidence: 99%
“…The checkpoint kinase CHK1 is a canonical substrate for ATR in replicating cells exposed to DNA damaging agents. However, in non-cycling cells, CHK1 protein is not present (19, 27, 28) and therefore no CHK1 phosphorylation is observed following exposure to NA-AAF (Figure 2A).ATR has been shown to phosphorylate itself on Thr1989 in asynchronous populations of cells exposed to inducers of replication stress (43,44). To determine whether this residue becomes phosphorylated in non-replicating cells, I exposed both cycling and non-cycling cells to NA-AAF and then monitored Thr1989 phosphorylation by immunoblotting.…”
mentioning
confidence: 99%